2010
DOI: 10.1021/jm1010995
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Kinase Inhibitors Based on the Imidazo[1,2-a]pyrazine Core: Fluorine and Deuterium Incorporation Improve Oral Absorption and Exposure

Abstract: Aurora kinases are cell cycle regulated serine/threonine kinases that have been linked to cancer. Compound 1 was identified as a potent Aurora inhibitor but lacked oral bioavailability. Optimization of 1 led to the discovery of a series of fluoroamine and deuterated analogues, exemplified by compound 25, with an improved pharmacokinetic profile. We found that blocking oxidative metabolism at the benzylic position and decreasing the basicity of the amine are important to obtaining compounds with good biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…Rat PK of selected aurora kinase inhibitors. 34 All compounds had IC 50 at Aurora A and Aurora B of ≤4 and ≤13 nM, respectively. The po AUC was determined in SD rats from 0−6 h after a 10 mg/kg oral dose.…”
Section: ■ Saturated Heterocyclesmentioning
confidence: 97%
See 1 more Smart Citation
“…Rat PK of selected aurora kinase inhibitors. 34 All compounds had IC 50 at Aurora A and Aurora B of ≤4 and ≤13 nM, respectively. The po AUC was determined in SD rats from 0−6 h after a 10 mg/kg oral dose.…”
Section: ■ Saturated Heterocyclesmentioning
confidence: 97%
“…34 One of their more advanced compounds in the paper contained a 4-fluoropiperidine (24), which had a rat oral AUC of 2.2 μM·h. To further improve the PK, the 4,4-difluoro analogue (25) was prepared, but it had a lower rat oral AUC.…”
Section: ■ Saturated Heterocyclesmentioning
confidence: 99%
“…103 However, this compound exhibited poor oral bioavailability in the rat due to a combination of poor absorption and rapid metabolism with the AUC reported as zero μM·h. Metabolite identification studies using radiolabeled material revealed that N-dealkylation of the amine moiety, which was known to project into solvent when bound to the enzyme, was the primary clearance pathway.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…[1, 2] Thus the introduction of fluorine has been especially valuable in the process of drug discovery to fine tune many different target and off-target related properties. [36] For example, fluorine has been used to increase the binding affinity of small molecules to its target, [7] to tune the pK B and logD, [8] to improve target selectivity, [9] to improve oral absorption and exposure, [10] to prevent from metabolism [11] or to increase the antibacterial spectrum. [12] Not surprisingly, an estimated 20% of all pharmaceuticals contain fluorine.…”
mentioning
confidence: 99%